Adenomyosis- surgical treatment for women’s infertility Laparotomy with Osada technique - I Nyoman Hariyasa Sanjaya; Cokorda Istri Mirayani Pemayun; Ni Komang Anik Pirgantari; Made Diah Vendita Sakuntari; Ni Wayan Dewi Purwanti; Ni Putu Nining Gianni; Ni Luh Made Diah Mas Cahyani Putri; Ni Luh Md Dwi Laxmi Satriani; Firsta Sesarina Mintariani; Anak Agung Wahyu Putri Agustini; Ketut Widyani Astuti (Indonesian Journal of Perinatology, 2022)
Introduction: Adenomyosis became challenging in the gynecological field and healthcare economic aspect. The prevalence of adenomyosis is widely ranged in different countries. Infertility is one of the frightening complications. Thus a radical adenomyosis tissue removal method using the triple-flap (the Osada technique) could be done. Using this technique the adenomyosis tissue can be removed as much as possible while maintaining normal uterine function. Thus, in this case, report, we performed a woman diagnosed with adenomyosis underwent the surgery with Osada technique. Case description: A 30-year-old woman went to the medical care of Kasih Medika. She has been married for 4,5 years and did not have any children. She had a history of abdominal pain every menstruation, and it has persisted since 2 months ago even though not on the menstrual schedule. Transvaginal sonographic examination revealed a diffusely enlarged uterus and thickening of the uterine wall. A laparotomy is performed using the Osada technique (triple flap. After that, around 1 month after surgery, the patient will undergo an ultrasound examination and the patient will undergo the GnRH agonist therapy (Tapros) 3 times. Conclusion: Adenomyosis is one of the challenging diseases. Adequate treatment must be done to minimalize the infertile probability Laparotomy with the Osada technique could be done. Infertility examination in both couples also must be done. Undergoing the GnRH agonist therapy also can give a better result for the patient.